The New Woman: Male anxieties and female circumvention in Berlin cabaret (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The New Woman was a complex, multidimensional, heterogeneous and gradual phenomenon that gained strength in Germany during the Weimar Republic. The right to female participation in politics guaranteed by the 1919 Constitution and the influx of women in the labor market generated male tensions about gender roles. Cabaret worked as a commentator of its time and shed light on the masculine anxieties regarding the New Woman, representing them through typifications. This article intends to analyze some of these typifications - evidence of male concerns - in counterpoint to female strategies to circumvent them.
Keywords: New Woman; Cabaret; Typifications; Weimar Republic